2019
DOI: 10.1016/j.dental.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Pulp capping materials modulate the balance between inflammation and regeneration

Abstract: The interrelations between inflammation and regeneration are of particular significance within the dental pulp tissue inextensible environment. Recent data have demonstrated the pulp capacity to respond to insults by initiating an inflammatory reaction and dentin pulp regeneration. Different study models have been developed in vitro and in vivo to investigate the initial steps of pulp inflammation and regeneration. These include endothelial cell interaction with inflammatory cells, stem cell interaction with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 63 publications
3
73
1
17
Order By: Relevance
“…It can be stated that compared with calcium silicates, resin-containing materials are not fully consistent with the spirit of DPC. On the contrary, calcium silicate materials such as Biodentine and MTA shift the balance towards regeneration, resulting in successful clinical outcomes [138]. However, a recent in vivo study concluded that ACTIVA BioACTIVE BASE/LINER exhibited excellent biocompatibility and healing for rat subcutaneous tissues in comparison with CSMs (MTA-HP and iRoot BP Plus) [139].…”
Section: Activa Bioactivementioning
confidence: 99%
“…It can be stated that compared with calcium silicates, resin-containing materials are not fully consistent with the spirit of DPC. On the contrary, calcium silicate materials such as Biodentine and MTA shift the balance towards regeneration, resulting in successful clinical outcomes [138]. However, a recent in vivo study concluded that ACTIVA BioACTIVE BASE/LINER exhibited excellent biocompatibility and healing for rat subcutaneous tissues in comparison with CSMs (MTA-HP and iRoot BP Plus) [139].…”
Section: Activa Bioactivementioning
confidence: 99%
“…Numerous investigations have concerned that the biological behaviors of DPSCs could be affected and amplified by extracellular environment [35]. Nowadays, an increasing focus on the design of new materials has emerged which are capable of driving DPSC migration and differentiation in dental therapy [36]. Among these, the CS/β-GP hydrogel has been widely used in drug delivery or tissue engineering systems for its biodegradability, biocompatibility, and antibacterial property [37].…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Different therapies for pulp disease can be selected according to the evaluation of pulp inflammation. Given the importance of tooth preservation, vital pulp therapies such as pulp capping, pulpotomy, and stepwise excavation of caries may be more appropriate than root canal treatment under some circumstances [8]. Currently, guided by the criteria of the American Association of Endodontists (AAE), medical history and clinical examination are the main methods used to evaluate pulp inflammation severity, considering information such as pain quality and history and responses to pulp sensitivity tests [9].…”
Section: Introductionmentioning
confidence: 99%